Coating composition for a sensor cover and sensor cover

CN122917652APending Publication Date: 2026-10-16HYUNDAI MOTOR CO LTD +3
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511064241.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2025-04-08
Filing Date
2025-07-31
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0005]LiDAR传感器主要位于车辆的前部和上部,除LiDAR传感器外,还有多种暴露在车辆外部的传感器容易不可避免地受到外部因素损坏

Benefits of technology

[0027] The coating composition disclosed in the embodiments of the present invention exhibits superior self-healing properties compared to existing coatings. Furthermore, due to the controllable self-healing time and curing speed, a coating with the desired hardness and self-healing properties can be achieved. Peel resistance and pencil hardness tests demonstrate that its self-healing time is faster than that of existing coatings.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122917652A_ABST
    Figure CN122917652A_ABST
Patent Text Reader

Abstract

The present invention relates to a coating composition for a sensor cover. The coating composition includes a polyaspartic acid resin and an acrylic polyol resin, wherein the polyaspartic acid resin and the acrylic polyol resin are mixed at a ratio of 99:1 to 60:40. The present invention also relates to a sensor cover. The sensor cover includes a base layer and a protective layer coated on the base layer. The coating composition formed on the protective layer includes a first polyaspartic acid resin and a second polyaspartic acid resin and an acrylic resin. The first polyaspartic acid resin and the second polyaspartic acid resin are mixed with the acrylic resin at a ratio of 99:1 to 60:40.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] Embodiments of the present invention relate to forming a coating composition for use in a sensor transparent cover coating and a sensor cover. Background Technology

[0002] With the increasing importance of autonomous driving, light detection and ranging (LiDAR) units, used to detect obstacles near vehicles, have been installed on vehicles.

[0003] LiDAR detects objects by emitting infrared light, based on the light reflected from the object.

[0004] LiDAR sensor covers primarily focus on simple protective functions, and these covers are mainly made of plastic, glass, or other materials.

[0005] LiDAR sensors are mainly located at the front and upper part of the vehicle. In addition to LiDAR sensors, there are many other sensors exposed outside the vehicle that are easily and inevitably damaged by external factors.

[0006] Furthermore, damage to the sensor cover can lead to a decrease in the sensor's sensing performance, which is an even more significant issue for autonomous driving.

[0007] Therefore, the sensor cover can be coated with a protective layer to protect the sensor cover, and the protective layer typically requires 2 to 24 hours to self-restore against external damage at room temperature.

[0008] The above description in the background art is intended to help understand the background of the present invention, and may include content unrelated to related technologies known to those skilled in the art. Summary of the Invention

[0009] The embodiments of the present invention are intended to solve the above-mentioned problems and aim to provide a coating composition for a sensor cover and a sensor cover, the coating composition being used to protect the sensor cover and having improved self-healing function compared to conventional coatings for sensor covers.

[0010] The coating composition for a sensor cover according to an embodiment of the present invention includes polyaspartic resin and acrylic polyol resin, wherein the polyaspartic resin and acrylic polyol resin are mixed in a ratio of 99:1 to 60:40.

[0011] Polyaspartic resin includes a first polyaspartic resin and a second polyaspartic resin.

[0012] In addition, the first polyaspartic resin and the second polyaspartic resin are mixed in a ratio of 9:1 to 7:3.

[0013] Specifically, the first polyaspartic acid resin has an amine value (mg KOH / g) of 196–204 and a molecular weight (Mw) of 500–600; the second polyaspartic acid resin has an amine value (mg KOH / g) of 188–196 and a molecular weight (Mw) of 600–700.

[0014] In addition, acrylic polyol resins include 110 to 120 hydroxyl groups (-OH groups) and have a molecular weight (Mw) of 8,000 to 10,000.

[0015] In addition, an isocyanate curing agent is mixed in an amount of 50 to 150% by weight based on 100% by weight of polyaspartic resin.

[0016] In one embodiment, the isocyanate curing agent includes a first isocyanate curing agent and a second isocyanate curing agent, and the first isocyanate curing agent and the second isocyanate curing agent can be mixed in a ratio of 1:9 to 5:5.

[0017] In the coating composition for a sensor cover according to an embodiment of the present invention, a first polyaspartic resin and a second polyaspartic resin are mixed in a ratio of 9:1 to 7:3.

[0018] The first polyaspartic acid resin has an amine value (mg KOH / g) of 196–204 and a molecular weight (Mw) of 500–600 g / mol; the second polyaspartic acid resin has an amine value (mg KOH / g) of 188–196 and a molecular weight (Mw) of 600–700 g / mol.

[0019] In addition, acrylic polyol resins include 110 to 120 hydroxyl groups (-OH groups) and have a molecular weight (Mw) of 8,000 to 10,000 g / mol.

[0020] In addition, based on 100% by weight of polyaspartic acid resin, an isocyanate curing agent is mixed in an amount of 50 to 150% by weight, and the first isocyanate resin and the second isocyanate resin are mixed in a ratio of 1:9 to 5:5.

[0021] According to an embodiment of the present invention, the sensor cover includes a base layer and a protective layer coated on the base layer, wherein the coating composition forming the protective layer includes a first polyaspartic resin, a second polyaspartic resin, and an acrylic polyol resin, and the first polyaspartic resin, the second polyaspartic resin, and the acrylic polyol resin are mixed in a ratio of 99:1 to 60:40.

[0022] The first polyaspartic resin and the second polyaspartic resin are mixed in a ratio of 9:1 to 7:3.

[0023] In addition, the first polyaspartic acid resin has an amine value (mg KOH / g) of 196–204 and a molecular weight (Mw) of 500–600; the second polyaspartic acid resin has an amine value (mg KOH / g) of 188–196 and a molecular weight (Mw) of 600–700.

[0024] In addition, acrylic polyol resins include 110 to 120 hydroxyl groups (-OH groups) and have a molecular weight (Mw) of 8,000 to 10,000.

[0025] In addition, an isocyanate curing agent is mixed in an amount of 50 to 150% by weight based on 100% by weight of the first polyaspartic resin and the second polyaspartic resin.

[0026] The coating composition according to embodiments of the present invention has superior self-healing properties compared to conventional coatings. By having adjustable self-healing time and curing speed, a coating with desired hardness and self-healing properties can be achieved.

[0027] The coating composition disclosed in the embodiments of the present invention exhibits superior self-healing properties compared to existing coatings. Furthermore, due to the controllable self-healing time and curing speed, a coating with the desired hardness and self-healing properties can be achieved. Peel resistance and pencil hardness tests demonstrate that its self-healing time is faster than that of existing coatings.

[0028] Chipping resistance and pencil hardness tests show that the coating composition of the present invention has a faster self-recovery time than existing coatings. Attached Figure Description

[0029] Figure 1 The sensor cover (prior art) is shown schematically.

[0030] Figure 2 This is the reaction mechanism of conventional coating compositions (existing technology).

[0031] Figure 3 This describes the reaction mechanism of the coating composition according to embodiments of the present invention.

[0032] Figure 4 This is an example of a standard coating scratch resistance test. Figure 5 This is an example of a scratch resistance test of a coating layer according to an embodiment of the present invention.

[0033] Figure 6 This is the state before a standard coating anti-cracking test. Figure 7 This is the state after a standard coating anti-cracking test.

[0034] Figure 8 This is the state of the coating before the chipping resistance test according to the embodiments of the present invention. Figure 9 This is the state of the coating after the crack resistance test according to the embodiment of the present invention.

[0035] Figure 10 This is the state before a standard coated pencil hardness test. Figure 11 and Figure 12 This is the state after a standard coating pencil hardness test.

[0036] Figure 13 This is the state of the coated pencil before the hardness test according to an embodiment of the present invention. Figure 14 and Figure 15 This is the state of the coated pencil after hardness testing according to an embodiment of the present invention. Detailed Implementation

[0037] To fully understand the present invention, its operational advantages, and the objectives to be achieved by practicing the present invention, reference should be made to the accompanying drawings illustrating exemplary embodiments of the present invention and the descriptions therein.

[0038] In describing exemplary embodiments of the present invention, descriptions of known technologies or repetitive descriptions may unnecessarily obscure the gist of the invention and have been reduced or omitted.

[0039] Figure 1 The sensor cover is shown schematically. Furthermore, Figure 2 This is the reaction mechanism of conventional coating compositions. Figure 3 This describes the reaction mechanism of the coating composition according to embodiments of the present invention.

[0040] The following is for reference Figures 1 to 3 A coating composition for a sensor cover and a sensor cover according to an embodiment of the present invention will be described.

[0041] The coating composition of this invention is a composition for coating a protective layer on a sensor cover, and can be applied to sensor covers installed on vehicles, including LiDAR sensors.

[0042] like Figure 1As shown, the protective layer 30 can be coated on a base layer 11 such as glass, polycarbonate (PC), etc., which transmits light from the sensor 20, and a film layer 12 with transparency, low reflectivity, design pattern or color can be inserted on the base layer 11.

[0043] External damage to the conventional protective layer requires 2 to 24 hours to self-recover at room temperature. The scratch test is conducted as follows: a 100 mm scratch is made on the surface of the sample product or a test sample manufactured under the same conditions as the sample product by applying a load of 9.8 N (Newtons) and a speed of 100 mm / s. The surface condition is then observed for 2 hours according to JIS (Japanese Industrial Standard) K 6718.

[0044] In contrast, embodiments of the present invention aim to use the Erichsen scratch tester method to confirm self-recovery performance, which is subject to more stringent conditions than conventional testing methods and is designed to achieve high hardness and elasticity self-recovery within 1 minute.

[0045] This is a very important part for continuously operating autonomous driving sensors (LiDAR) (especially since sensing performance can drop by about 30% to 50% when scratches occur).

[0046] In the prior art, the resin compositions used for protective layers are mainly composed of polyester polyols, polycarbonate polyols and acrylic polyols, thus requiring slow curing speeds, post-drying, and organometallic catalysts.

[0047] like Figure 2 As shown, the resin composition has a single polyurethane reaction mechanism in which the polyol is combined with the isocyanate.

[0048] However, embodiments of the present invention consist of a polyurethane composition combining polyaspartic acid (superior concept: polyester) and polyol, thereby enabling rapid and controllable curing speed.

[0049] Furthermore, the subsequent drying process is unnecessary or only takes a very short time, and the organometallic catalyst is only needed in trace amounts or is no longer necessary.

[0050] like Figure 3 As shown, the coating composition for the sensor cover according to the embodiments of the present invention, as a thermosetting polyurethane, has two reaction mechanisms.

[0051] Polyurethane reactions are formed by combining polyols with isocyanates, while polyurea reactions are formed by combining polyaspartic resins with isocyanates, as shown below.

[0052] Hydroxyl group (-OH) + isocyanate group (-NCO) → form urethane bond (-NHCOO-).

[0053] Amine group (-NH) + isocyanate group (-NCO) → form urea bond (-NHCONH-).

[0054] The polyurethane composition, namely the coating composition of the embodiments of the present invention, comprises polyaspartic acid resin, acrylic polyol and isocyanate-based curing agent.

[0055] In addition, the polyurethane composition may include two polyaspartic resins (e.g., a first polyaspartic resin and a second polyaspartic resin).

[0056] The first polyaspartic acid resin has a solid content of 100%, an amine value (mgKOH / g) in the range of 196 to 204, a molecular weight (Mw) in the range of 500 to 600, and its characteristics include rapid hardening, high weather resistance, and room temperature drying.

[0057] The second polyaspartic acid resin has a solid content of 100%, an amine value (mgKOH / g) in the range of 188 to 196, a molecular weight (Mw) in the range of 600 to 700, and is characterized by a long working life, high weather resistance, and excellent appearance.

[0058] When the first polyaspartic resin and the second polyaspartic resin are mixed in an appropriate ratio (9:1 to 7:3), the operating time and curing speed can be controlled, and an excellent appearance can be formed.

[0059] Because the first polyaspartic resin has a short working time and poor external gloss, while the second polyaspartic resin has a long working time and excellent external gloss, the optimal ratio of the first and second polyaspartic resins must be selected. Exceeding this range, with too short or too long a working time, will result in poor workability and appearance.

[0060] The acrylic polyol resin has a solids content of 60%, a hydroxyl group (-OH group) of 110-120 (based on solids), a glass transition temperature (Tg) of 2 degrees, and a molecular weight (Mw) of 8,000-10,000.

[0061] Acrylic polyol resins possess excellent adhesion, flexibility, scratch recovery, and self-healing properties.

[0062] The ratio of polyaspartic acid resin to acrylic polyol resin is 99:1 to 60:40.

[0063] This enables excellent adhesion, flexibility, scratch recovery, and self-healing properties, and the acrylic polyol resin shortens the curing time and complements the aforementioned physical properties.

[0064] When the content of acrylic polyol resin is less than 1%, the adhesion decreases; when it exceeds 40%, the curing time is prolonged.

[0065] The solid content of isocyanate A can be 100%, the isocyanate group (NCO) is in the range of 23% to 24%, and the equivalent of aliphatic HDI trimer (isocyanurate) is 177 to 181 (eq).

[0066] Isocyanate A is widely used in industrial coatings for vehicle refinishing due to its non-yellowing properties and excellent weather resistance, hardness, and mechanical properties.

[0067] The solid content of isocyanate B can be 90%, NCO 8%–9%, ​​and the equivalent of aliphatic HDI trimer (adduct) is 492–496 (eq).

[0068] Isocyanate B does not yellow, exhibits excellent weather resistance, and provides elasticity without the addition of plasticizers. Furthermore, its self-healing properties improve with increasing isocyanate B content.

[0069] The appropriate ratio of two curing agents can provide the required hardness and elasticity.

[0070] For example, the ratio of aliphatic polyisocyanate A to hexamethylene diisocyanate B, which has elastic properties, is 1:9 to 5:5, and the required hardness and elasticity can be adjusted within the corresponding range.

[0071] In addition, the self-healing and curing speeds can be adjusted.

[0072] For hard segment regulation, when the isocyanate A content is high, self-recovery is very slow due to changes in hardness. When the isocyanate B content is high, scratch recovery is fast due to changes in softness, but physical properties are poor.

[0073] It may also include UV absorbers, light stabilizers, leveling agents and defoamers, and includes UV absorbers due to their lightfastness to prevent yellowing and discoloration.

[0074] Based on a mixture of 100% by weight polyurethane main components polyaspartic acid and acrylic polyol, the amount of ultraviolet absorber can be 0.1 to 2% by weight.

[0075] The type of ultraviolet absorber is a triazine material, whose chemical composition can be a mixture of 2-[4-[(2-hydroxy-3-dodecanoyloxypropyl)oxy]-2-hydroxyphenyl]-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine and 2-[4-[(2-hydroxy-3-decadecanoyloxypropyl)oxy]-2-hydroxyphenyl]-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine.

[0076] The light stabilizer is a hindered amine light stabilizer (HALS), whose chemical composition can be a mixture of bis-(1-octoxy-2,2,6,6-tetramethyl-4-piperidinyl) sebacate.

[0077] Based on 100% by weight of the main polyurethane components polyaspartic acid and polyol, the amount of ultraviolet absorber can be 0.1 to 2% by weight.

[0078] Furthermore, when the amount of ultraviolet absorber and light stabilizer exceeds 6% by weight, the mechanical properties of embodiments of the present invention may deteriorate.

[0079] Leveling agent A is mainly composed of polyether-modified polydimethylsiloxane, which improves the wettability of materials, prevents pinholes, and provides surface slippage.

[0080] Typical properties are: density (20℃) of 0.93 g / mol, solid content (30 mm, 150℃) of 12.5%, solvent xylene / monophenylethylene glycol = 7 / 2, and flash point of 25℃.

[0081] The amount of leveling agent A can be 1 to 3 by weight, based on a mixture of 100% by weight of polyurethane main components polyaspartic acid and acrylic polyol.

[0082] Leveling agent B is mainly composed of silicone-modified polyacrylate containing OH functional groups. It can participate in the cross-linking of polymers through hydroxyl reactions. When it is deposited on the coating surface, it can maintain its performance for a long time and can significantly improve water and oil repellency by increasing hydrophobicity.

[0083] Typical properties are: density (20℃) 1.00 g / mol, solid content (30 mm, 150℃) 25%, solvent is methoxypropyl acetate, flash point is 43℃, and OH value is 30 mg KOH / g.

[0084] Based on 100% by weight of the main polyurethane components polyaspartic acid and polyol, the amount of leveling agent B can be 1 to 7% by weight.

[0085] Defoamers are fluorine-modified silicone-containing defoamers that reduce bubble formation during application and quickly eliminate bubbles by causing them to float during vacuum defoaming.

[0086] Typical properties include: active ingredient content of over 95%, density (20℃) of 0.80–0.82 g / mol, and flash point of 49℃.

[0087] Based on 100% by weight of polyurethane main components polyaspartic acid and polyol, the amount of defoamer can be 0.1 to 1% by weight; based on 100% by weight of isocyanate, the amount of defoamer can be 0.1 to 1% by weight.

[0088] According to an embodiment of the present invention, the sensor cover is coated with a polyurethane coating composition having the above-described composition by reaction injection molding.

[0089] In other words, the coating composition is prepared by injecting two liquid raw materials (polyol and isocyanate) into a sealed mold and allowing them to cure rapidly in a short time.

[0090] The following describes the test results of the coatings manufactured using the coating compositions according to embodiments of the present invention.

[0091] The self-healing properties of the compositions according to embodiments of the present invention were tested using the Taguchi experimental design method.

[0092] The testing method is as follows: mix the main components of the composition with isocyanate (3-5 minutes), defoam under vacuum (5-10 minutes), inject into a mold (10 minutes), and then cure at room temperature or 60°C for 24 hours to prepare a sample.

[0093] The curing speed was determined by the time of gelation, and the self-healing was measured by visually observing the self-healing through a scratch test after complete curing and measuring the time.

[0094] The three levels and four factors are shown in Table 1, and Table 2 shows the test cases and test results.

[0095] Table 1

[0096]

[0097] Table 2

[0098]

[0099] The scratch resistance test is as follows.

[0100] After scratching the surface of the test product or a test sample manufactured under equivalent conditions, the surface condition is evaluated using the following table according to the Erichsen scratch evaluation method of ISO 1518-1.

[0101] Table 3

[0102] grade Appearance 5 Surface damage is not visible 4 Minor visible surface damage 3 The surface damage is minor and visible but not serious. 2 Surface damage is visible 1 Surface damage is clearly visible.

[0103] Therefore, as Figure 4 As shown, the prior art observation is Level 1, such as... Figure 5 As shown, the observation level of the embodiment of the present invention is 4 or above (required time 1 minute).

[0104] Therefore, it can be seen that the coating composition of the embodiments of the present invention has better self-healing properties than conventional coating compositions.

[0105] Figure 6 This is the state before a standard coating anti-cracking test. Figure 7 This is the state after a standard coating anti-cracking test. Furthermore, Figure 8 This is the state of the coating before the chipping resistance test according to the embodiment of the present invention. Figure 9 This is the state of the coating after the crack resistance test according to the embodiment of the present invention.

[0106] The spalling resistance test is as follows.

[0107] The chipping resistance test was conducted using test stones (Gravelometer: SAE J400 standard product) on test samples cut from the test product. However, in the case of low-temperature testing, the test samples were stored in a freezer (-40°C) for at least 3 hours before testing. After testing, dust was removed from the surface of the test samples by blowing air, and their appearance was visually evaluated.

[0108] As shown in the figure, the test results show that the appearance scratch resistance of the present invention is better than that of conventional products.

[0109] After a maximum of 168 hours, the results showed that conventional products exhibited similar self-healing after testing, but the scratch self-healing of the embodiments of the present invention was similar.

[0110] The test results show that the present invention is superior to conventional products in terms of self-healing of external scratches, but its resistance to cracking should be even better from the beginning.

[0111] Figure 10 This is the state of the conventional coating before the pencil hardness test. Figure 11 and Figure 12 This is the state of a standard coating after a pencil hardness test. Furthermore, Figure 13This is the state of the coating in the embodiment of the present invention before the pencil hardness test. Figure 14 and Figure 15 This is the state of the coating according to the embodiment of the present invention after a pencil hardness test.

[0112] Figure 12 and Figure 14 These are the observations after the test. Figure 13 and Figure 15 The results were observed 24 hours later at room temperature (20-25°C).

[0113] In conventional coatings, the coating is good at pencil hardness B, unacceptable at BH to 6H, and good after 24 hours.

[0114] In the embodiments of the present invention, a hardness of B to 6H after testing is good, so no inspection is required after 24 hours.

[0115] The scratch test results confirm that the self-recovery time of this invention is faster than that of conventional products.

[0116] As described above, since the coating composition of the present invention has excellent self-healing properties compared with conventional coatings, and its self-healing time and curing speed can be adjusted, it is possible to achieve a coating with the desired hardness and self-healing properties.

[0117] Therefore, when coatings are applied to the sensor covers of various sensors (especially autonomous driving sensors), the coatings help maintain the performance of the sensors.

[0118] Although the invention has been described above in conjunction with the accompanying drawings, it is not limited to the described embodiments, and those skilled in the art will readily recognize that various modifications and alterations can be made without departing from the spirit and scope of the invention. Therefore, examples of such modifications or alterations should be included in the claims, and the scope of the invention should be interpreted based on the appended claims.

Claims

1. A coating composition for a sensor cover, the coating composition comprising: Polyaspartic acid resin; and Acrylic polyol resin, among which, The polyaspartic acid resin and the acrylic polyol resin are mixed in a ratio of 99:1 to 60:

40.

2. The coating composition according to claim 1, wherein, The polyaspartic acid resin includes a first polyaspartic acid resin and a second polyaspartic acid resin.

3. The coating composition according to claim 2, wherein, The first polyaspartic resin and the second polyaspartic resin are mixed in a ratio of 9:1 to 7:

3.

4. The coating composition according to claim 2, wherein, The first polyaspartic acid resin has an amine value in the range of 196 to 204 mg KOH / g and a molecular weight Mw in the range of 500 to 600, while the second polyaspartic acid resin has an amine value in the range of 188 to 196 mg KOH / g and a molecular weight Mw in the range of 600 to 700.

5. The coating composition according to claim 2, wherein, The acrylic polyol resin includes 110 to 120 hydroxyl-OH groups and has a molecular weight (Mw) in the range of 8,000 to 10,000.

6. The coating composition according to claim 2, wherein, Based on 100% by weight of the polyaspartic resin, an isocyanate curing agent is mixed in an amount ranging from 50% to 150% by weight.

7. The coating composition according to claim 6, wherein, The isocyanate curing agent includes a first isocyanate curing agent and a second isocyanate curing agent.

8. The coating composition according to claim 7, wherein, The first isocyanate curing agent and the second isocyanate curing agent are mixed in a ratio of 1:9 to 5:

5.

9. The coating composition according to claim 7, wherein, The first polyaspartic resin and the second polyaspartic resin are mixed in a ratio of 9:1 to 7:

3.

10. The coating composition according to claim 9, wherein, The first polyaspartic acid resin has an amine value in the range of 196 to 204 mg KOH / g and a molecular weight Mw in the range of 500 to 600, while the second polyaspartic acid resin has an amine value in the range of 188 to 196 mg KOH / g and a molecular weight Mw in the range of 600 to 700.

11. The coating composition according to claim 9, wherein, The acrylic polyol resin includes 110 to 120 hydroxyl-OH groups and has a molecular weight (Mw) in the range of 8,000 to 10,000.

12. The coating composition according to claim 9, wherein, Based on 100% by weight of the polyaspartic resin, an isocyanate curing agent is mixed in an amount ranging from 50% to 150% by weight.

13. The coating composition according to claim 12, wherein, The isocyanate curing agent includes a first isocyanate curing agent and a second isocyanate curing agent, and the first isocyanate curing agent and the second isocyanate curing agent are mixed in a ratio of 1:9 to 5:

5.

14. A sensor cover comprising: grassroots level; and A protective layer coated on the base layer, The coating composition forming the protective layer includes: First polyaspartic resin and second polyaspartic resin; and Acrylic polyol resin, among which, The first polyaspartic resin and the second polyaspartic resin are mixed with the acrylic polyol resin in a ratio of 99:1 to 60:

40.

15. The sensor cover according to claim 14, wherein, The first polyaspartic resin and the second polyaspartic resin are mixed in a ratio of 9:1 to 7:

3.

16. The sensor cover according to claim 14, wherein, The first polyaspartic acid resin has an amine value in the range of 196 to 204 mg KOH / g and a molecular weight Mw in the range of 500 to 600, while the second polyaspartic acid resin has an amine value in the range of 188 to 196 mg KOH / g and a molecular weight Mw in the range of 600 to 700.

17. The sensor cover according to claim 14, wherein, The acrylic polyol resin includes 110 to 120 hydroxyl-OH groups and has a molecular weight (Mw) in the range of 8,000 to 10,000.

18. The sensor cover according to claim 14, wherein, An isocyanate curing agent is mixed in an amount ranging from 50% to 150% by weight based on 100% by weight of the first polyaspartic resin and the second polyaspartic resin.